TEKNIK MODELING UNTUK MENINGKATKAN KECERDASAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN DI RA AL-IKHLAS CIBALONG - Siti Alifya Shafira, Alifya (2022)
In essence, man is a creature that needs others in life. An aspect that must be improved in establishing relationships is social emotional intelligence. Early childhood needs to develop social-emotional intelligence in order to experience a meaningful life in the future. The reality in RA Al-Ikhlas Cibalong revealed that the social emotional intelligence of children aged 5-6 years was in the category of starting to develop by 93.3% and the category began to develop by 6.7%. One of the techniques for developing social emotional intelligence in RA Al-Ikhlas Cibalong is through modeling techniques. Human behavior is not only influenced by the process of learning from the environment, but can also be through direct observation of the behavior of others. Through this technique the child can imitate the displayed model. The modeling technique used is a dual modeling technique where researchers combine direct modeling with symbolic modeling. The research method used is a class action research with the aim of knowing the improvement of social emotional intelligence through modeling techniques in children aged 5-6 among them 7 boys and 8 girls in RA Al-Ikhlas Cibalong. Before performing the action the researcher conducts a preliminary study and gets the results of the pre-cycle and the action performed consists of 2 cycles with 3 meetings on each cycle. The result of this study is that children aged 5-6 years have increased emotional social intelligence by 26% for the category of developing as expected and 40% for the category of developing very well.